Obstacles in Preventing Action Against a Gambling Crime - Hida, Rian Yunus (Estudiante Law Journal, 2024)
Abstract: This study aims to determine precautions Against A Gambling Crime. The method in this research is empirical research methodology and uses a qualitative approach to descriptive qualitative analysis techniques. The results of this study are precautions against gambling crimes committed by the police are that the public hide information related to these crimes, insufficient evidence, and a lack of investigative resources. Some of these points in general can provide obstacles for law enforcers in carrying out their duties and responsibilities. In carrying out these duties and authorities, the Indonesian National Police always acts based on legal norms and respects religious norms, decency, decency, and upholds human rights. The public should not be secretive and be more open in providing information and reports to the Police regarding gambling crimes that occur around the area where they live,